2006
DOI: 10.1113/jphysiol.2006.115287
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of hippocampal plasticity‐related gene expression by sleep deprivation in rats

Abstract: Previous work shows that sleep deprivation impairs hippocampal-dependent learning and long-term potentiation (LTP). Brain-derived neurotrophic factor (BDNF), cAMP response-element-binding (CREB) and calcium-calmodulin-dependent protein kinase II (CAMKII) are critical modulators of hippocampal-dependent learning and LTP. In the present study we compared the effects of short-(8 h) and intermediate-term (48 h) sleep deprivation (SD) on the expression of BDNF and its downstream targets, Synapsin I, CREB and CAMKII… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
102
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(109 citation statements)
references
References 60 publications
(67 reference statements)
7
102
0
Order By: Relevance
“…Taishi et al (2001) found that after 8 h of sleep deprivation the immediate early gene Arc increased within the hippocampus, but the growth factor BDNF remained unchanged. However, Guzman-Marin et al (2006) gene expression were reduced after sleep deprivation. Our group has recently examined gene-expression changes specifically within the hippocampus after sleep deprivation using genome-wide microarray assays.…”
Section: Gene Expression As a Results Of Sleep Deprivationmentioning
confidence: 98%
“…Taishi et al (2001) found that after 8 h of sleep deprivation the immediate early gene Arc increased within the hippocampus, but the growth factor BDNF remained unchanged. However, Guzman-Marin et al (2006) gene expression were reduced after sleep deprivation. Our group has recently examined gene-expression changes specifically within the hippocampus after sleep deprivation using genome-wide microarray assays.…”
Section: Gene Expression As a Results Of Sleep Deprivationmentioning
confidence: 98%
“…Experimental studies show that prolonged sleep restriction or disruption affects hippocampal integrity (Guzman-Marin et al, 2006, Kopp et al, 2006, McDermott et al, 2003, Roman et al, 2005a. For example, in young male rats, one month of chronic sleep restriction reduced dorsal hippocampal volume by 10% (Novati et al, 2011).…”
Section: Sleep and Its Effect On Neuroprogressionmentioning
confidence: 99%
“…We interpret our finding as showing that the effects of PSI on sleep are mediated specifically by sleep-regulatory sites. Although PSI application in HIPPO is likely to affect local protein synthesis and hippocampal function, and sleep may facilitate synthesis of plasticity-related proteins such as brain derived neurotrophic factor (BDNF) in HIPPO (Guzman-Marin et al, 2006), our findings suggest that these interactions are not critically related to the control of sleep-wake states.…”
Section: Discussionmentioning
confidence: 83%
“…We have found that 48 h sleep deprivation reduces protein levels of brain-derived neurotrophic factor in hippocampus (Guzman-Marin et al, 2006).…”
mentioning
confidence: 99%